Prevalence, pattern and predictors of intimate partner violence amongst female undergraduates in Abia State, Nigeria; public health implications - Franklin Odini; Chidinma Amuzie; Kalu Ulu Kalu; Uche Nwamoh; Uloaku Emma-Ukaegbu; Michael Izuka; Uchechukwu Odini; Chukwubuike Ezepue (BMC, 2024)
Abstract Background Intimate Partner Violence (IPV) is the range of sexually, psychologically and physically coercive acts used against adult and adolescent women by a current or former male partner. It is a major public health problem globally. This study determined the prevalence, patterns and predictors of IPV amongst female undergraduates in Abia State. Methods A cross-sectional study was conducted from January - February 2022 amongst 306 female undergraduates in Abia State. A mixed method of an online structured questionnaire created on Google forms & onsite self-administered questionnaire were deployed for data collection. Descriptive, bivariate and multivariate analyses were done using IBM SPSS Version 26.0. The level of significance was set at 5%. Results A total of 306 respondents participated in the survey. The overall prevalence of IPV amongst female undergraduates was 51.2% (95% CI: 44.8-57.6%). Emotional abuse was the most common form of abuse 78.9%, followed by Physical abuse 42.0% and Sexual abuse 30.8%. Predictors of IPV reported include female earning/receiving more than their partner monthly (aOR = 2.30; 95% CI: 1.20-4.41); male (partner) alcohol consumption (aOR = 5.17; 95% CI: 2.46-10.88), being a smoker of cigarette/marijuana (aOR = 11.01; 95% CI: 1.26-96.25) and having witnessed domestic violence as a child (aOR = 3.55; 95% CI: I.56-8.07). Adverse effects such as unwanted pregnancies (12%), miscarriages (10%), eating/sleeping disorders (21%) and bruises (23%) amongst others were noted in some of the victims. Conclusion Over half of all female undergraduates in Abia State have experienced IPV with emotional abuse being the commonest. Some Individual and relationship factors were identified as predictors of IPV. We recommend intensifying primary prevention campaigns against risk factors identified like smoking and alcohol consumption.